Modeling and analysing the performance of a wireless mesh network - Zhou-Kangas, Yue (2014)
As an emerging technology for the future internet, the wireless mesh networks can provide fast-configure low-cost and scalable wireless networks to large are- as. The wireless community networks are based on the wireless mesh network technology as a new solution for internet access, game, internet radio and VoIP services for the users.